Laparoscopic Appendectomy does not Increase the Rate of Negative Appendectomy along with a Lower Rate of Perforated Appendicitis – Results in 1899 Patients at Zagreb UHC - Goran Augustin; Zrinka Čižmešija; Jurica Žedelj; Igor Petrović; Vanja Ivković; Anko Antabak; Davor Mijatović; Mate Škegro (Acta Clinica Croatica, 2018)
Laparoscopic appendectomy is the method of choice of many professional societies owing to its many advantages. The question arises whether surgeons urge more easily to laparoscopic exploration due to its less invasiveness, faster recovery and adequate exploration of the entire abdominal cavity than to observation in unequivocal cases. This retrospective analysis (2009-2016) included 1899 patients undergoing laparoscopic (lap) or gridiron intra-abdominal approach treated at Zagreb University Hospital Centre. The analysis included total negative appendectomy, negative-negative appendectomy (normal appendix and no other pathology found), and negative-positive appendectomy (normal appendix but another pathology found) in children (≤16 years) and adults. There was no statistically significant difference in the rates of negative appendectomy (children) – lap vs. open (p=0.24); negative appendectomy (adults) – lap vs. open (p=0.15); negative-negative appendectomy (children) – lap vs. open (p=0.36); negative-negative appendectomy (adults) – lap vs. open (p=0.21); negative-positive appendectomy (children) – lap vs. open (p=0.53); negative-positive appendectomy (adults) – lap vs. open (p=0.56); and laparoscopy group negative appendectomy in children vs. adults (p=0.56). There was a statistically significantly higher perforation rate with the open approach in total (p<0.0001), in children (p<0.0001) and in adults (p=0.02). There was no statistically significant difference between adults and children in the perforation rate with laparoscopic approach (p=0.24) and perforation rate with open approach (p=0.29). Results confirmed that there was no statistically significant difference in the rate of negative appendectomy in all subgroups. It is concluded that laparoscopic appendectomy should be offered as the method of choice in any patient population with suspicion of acute appendicitis.